Grandparents' childcare and female labor force participation - Josefina Posadas; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2012)
In the U.S., grandparents look after one in five preschool children of employed women. Does this source of informal childcare increase female labor force participation and if so, up to what extent? The main challenge to answer this question is that a positive relationship between grandparents' childcare and female labor force participation might not be causal. We use the maternal grandmother's death as an instrument of grandparents' childcare to measure the effect of grandparents' childcare on maternal labor force participation (MLFP). We compare OLS and IV estimates and find that grandparents' childcare increases MLFP by 15 percentage points on average. We argue that most of the effect is driven by families from socio-economically disadvantaged backgrounds.
urn:nbn:de:101:1-201206146792
Keywords: J2; I3; 330; maternal labor force participation; grandparents; childcare; NLSY